Serum levels of epithelial‐derived mediators and interleukin‐4/interleukin‐13 signaling after bronchial challenge with Dermatophagoides pteronyssinus in patients with allergic asthma - Kalinauskaite‐Zukauske, Virginija; Janulaityte, Ieva; Januskevicius, Andrius; Malakauskas, Kestutis (Scandinavian journal of immunology, 2019)
Allergens are the main trigger that enhances airway type 2 inflammation, and the epithelium is the first line of defense that reacts to its exposure. Therefore, epithelial‐derived mediators, such as interleukin (IL)‐25, IL‐33, thymic stromal lymphopoietin (TSLP) and ezrin, may play a role as alarmins in IL‐4/IL‐13 signaling in allergic asthma (AA). We investigated the serum levels of IL‐25, IL‐33, TSLP, ezrin, IL‐4 and IL‐13, after bronchial challenge with Dermatophagoides pteronyssinus in patients with AA. We examined 18 subjects: nine steroid‐free stable patients with AA sensitized to D. pteronyssinus and nine non‐atopic healthy subjects (HS). Bronchial allergen challenge was performed using inhaled D. pteronyssinus allergen. IL‐4, IL‐13, IL‐25, IL‐33, TSLP and ezrin levels in serum were measured by ELISA at two time points ‐ before and 24 hours after bronchial allergen challenge. The serum levels of IL‐25, TSLP and ezrin did not differ between AA and HS groups at baseline. However, after allergen exposure, significant increases in serum levels of IL‐25, TSLP and ezrin were observed only in patients with AA. The serum level of IL‐33 at baseline was significantly higher in the AA group compared with HS, but the allergen challenge did not provoke an increase of this cytokine in any group. IL‐4 and IL‐13 levels were significantly higher at baseline in the AA group compared with HS and, after allergen exposure, were significantly increased in the AA group, with no effect on HS. Thus, the epithelial‐derived mediators IL‐25, TSLP and ezrin, via IL4/IL13 signaling, enhance type 2 inflammation after bronchial challenge with D. pteronyssinus in AA.